2009
DOI: 10.2322/tstj.7.pk_7
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phase Delay Estimation in VRAD Mission of SELENE (KAGUYA)

Abstract: In the very long baseline interferometry (VLBI) radio sources mission of selenological and engineering explorer, the differential phase delay between the Rstar and Vstar sub-satellites is obtained by using the multifrequency VLBI method during the switching VLBI observation period. The cycle ambiguity is successfully determined and the differential phase delay is estimated within an error of 7 picoseconds. The RMS error is somewhat larger than that for the case of same-beam VLBI because fluctuations of propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…There were many opportunities to utilize the same beam differential VLBI method during this period and we have confirmed that the cycle ambiguity for the differential phase delay in the MFV method can be solved using the same beam differential VLBI method. An estimated differential phase delay for Okina and Ouna at 2212 MHz for the baseline between Ishigaki and Iriki stations is shown in Figure 6 as an example 18) . The error in the differential phase delay is smaller than 2 ps in a 30 s integration interval.…”
Section: Initial Resultsmentioning
confidence: 99%
“…There were many opportunities to utilize the same beam differential VLBI method during this period and we have confirmed that the cycle ambiguity for the differential phase delay in the MFV method can be solved using the same beam differential VLBI method. An estimated differential phase delay for Okina and Ouna at 2212 MHz for the baseline between Ishigaki and Iriki stations is shown in Figure 6 as an example 18) . The error in the differential phase delay is smaller than 2 ps in a 30 s integration interval.…”
Section: Initial Resultsmentioning
confidence: 99%